2005
DOI: 10.1093/eurpub/cki010
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of health system delay among confirmed tuberculosis cases in Spain

Abstract: Despite free health care being universally available in Spain, there are some groups of TB patients whose treatment is unduly delayed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 12 publications
2
20
1
2
Order By: Relevance
“…Even though the relationship between TB and silicosis is well documented, a study in Spain found that presence of silicosis was an independent risk factor for health system delay in diagnosing and treating patients with TB [103]. This may be due to the fact that the diagnosis of TB among silicotics can be very difficult, especially in lower grades, when the clinical manifestations can be benign and the radiological alterations can be indistinguishable from those resulting from the preexisting silicosis [104].…”
Section: Silicosismentioning
confidence: 99%
“…Even though the relationship between TB and silicosis is well documented, a study in Spain found that presence of silicosis was an independent risk factor for health system delay in diagnosing and treating patients with TB [103]. This may be due to the fact that the diagnosis of TB among silicotics can be very difficult, especially in lower grades, when the clinical manifestations can be benign and the radiological alterations can be indistinguishable from those resulting from the preexisting silicosis [104].…”
Section: Silicosismentioning
confidence: 99%
“…In a study conducted in Spain it was found that a factor related to a longer delay in the TB diagnosis was the fact that the symptomatic patient sought primary healthcare units which were not prepared for the performance of the diagnosis of the disease. In the same study, the fact that the patient with TB symptoms sought the hospital for care represented a decrease in the time between the onset of the symptoms and the diagnosis of the disease (5) .…”
mentioning
confidence: 91%
“…The increase in the delay in the performance of the diagnostic test and initiation of the treatment leads to an increased risk of disease transmission, especially in urban environments, and this condition of the healthcare services reduces the chance of a cure for the TB patient. Factors related to the patient and the health services can contribute to this delay in the performance of the TB diagnosis and many of these are interlinked to the organization of the health services, whether public or private (4)(5) . Studies carried out in different places such as Shanghai, Spain, Hong Kong and Brazil have shown that some of these factors are related to the kind of health service sought by the TB patient, the type of service that performs the diagnosis and the diagnostic tools employed by the healthcare service (4,6) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is a considerable problem in tuberculosis (TB), as it increases the infectious pool in the community (increases the time a patient stays infected) and also the mortality rate (1). This includes patient delay (PD) (from the onset of symptoms to the first contact with the health services) and health system delay (HSD) (from the first visit to the health services to the initiation of correct treatment) (2, 3). …”
mentioning
confidence: 99%